Soil-meteorological measurements at ICOS monitoring stations in terrestrial ecosystems - Beeck, M. de; Gielen, B.; Merbold, Lutz (Walter de Gruyter GmbH, 2018)
The Integrated Carbon Observation System is a pan-European research infrastructure providing standardized, long-term observations of greenhouse gas concentrations and earth-atmosphere greenhouse gas interactions. The terrestrial component of Integrated Carbon Observation System comprises a network of monitoring stations in terrestrial ecosystems where the principal activity is the measurement of ecosystem-atmosphere fluxes of greenhouse gases and energy by means of the eddy covariance technique. At each station a large set of ancillary variables needed for the interpretation of observed fluxes and for process studies is additionally monitored. This set includes a subset of variables that describe the thermal and moisture conditions of the soil and which are here conveniently referred to as soil-meteorological variables: soil temperature, volumetric soil water content, water table depth, and soil heat flux density. This paper describes the standard methodology that has been developped for the monitoring of these variables at the ecosystem stations.